La esclavitud indígena en Chile: argumentos, autoridades y pseudo-diálogo en el Tratado de Melchor Calderón. - Ambel, Karime Parodi (Colonial Latin American Review, 2019)
The article provides information on the slavery in Chile including indigenous groups rebelling to colonization, massive and devastating rebellions and importance and futility. Topics include management in a residence trials, management of the royal estate and ordinances to punish black slaves to flee their slaveholders.